OPTIMALISASI PROGRAM AKSELERASI PEMBELAJARAN TAHFIDZUL QUR’AN PADA LEMBAGA MADRASAH IBTIDAIYAH NAHDLATUL ULAMA KECAMATAN LEKOK KABUPATEN PASURUAN - Hamidah; Nailatul Khoiriyah Cholil, M.Pd.I. Naila (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2024)
This research aims to determine the optimization of the Tahfidzul Qur'an accelerated learning program at the Nahdlatul Ulama' Lekok Madrasah Ibtidaiyah institution in teaching and training students in memorizing the Al-Qur'an in its entirety Apart from that, the aim of this research is to find out how optimal the acceleration program is, the advantages and disadvantages of learning, the impact of the Tahfidzul Qur'an acceleration program with the aim of how optimal the Tahfidzul Qur'an learning acceleration program is at the Nahdlatul Ulama' Lekok madrasah institution.Tahfîz is the process of memorizing the verses of the Koran as a whole and protecting them from forgetting. The hafz is using certain methods for remembering. Since the time of Prophet Muhammad, these methods have largely been followed. Receiving a revelation from Jibril as such. Well, that's how Allah SWT does it. He's determined to preserve the authenticity of the Koran and the tradition that's inherent in Muslims. The study of tahfîz al-Qur'an has so far focused more on field studies in Islamic boarding schools and Al-Qur'an institutions, especially on success factors, systems, infrastructure, teacher qualifications, curriculum and learning outcomes . Thesis: